(untitled) (Research, Society and Development, 2025)
Objective: To share the experiences and knowledge acquired during the supervised internship in gym practices by undergraduate students in the Physical Education bachelor’s program, which took place in a gym located in the northern zone of Manaus-AM. Method: This is a descriptive study with a qualitative approach, understood as a method of investigation focused on the collection, analysis, and description of non-numerical data experienced by two students. Results and Discussion: After organizing and reading the collected material, the information was subjected to content analysis and divided into three main topics: types of services provided, the group with the greatest difficulties, and the students’ goals. Conclusion: The study, presented as an experience report, highlights the importance of the supervised internship in a gym setting, as it broadens the understanding of professional practice and serves as a crucial link between theory and practice.